Pengaruh Biaya Operasional Terhadap Laba Bersih - Dina Fitriasari; Rivan Syamsurijal Biya; Dede Nuraeni; Rachmat Agus Santoso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to obtain information regarding how much influence operational costs have on the amount of net profit obtained by a company and the author hopes that this research can provide benefits to the company's existence in order to maintain the continuity of a company's production process and provide motivation to become a better company. This research uses a descriptive-comparative research method with a qualitative approach. According to Adiputra et al., (2021) Descriptive research is research that aims to describe existing phenomena, namely natural phenomena or man-made phenomena, or that is used to analyze or describe the results of the subject, but is not intended to provide wider implications. Research using this method will determine significant relationships between the variables studied so that it will produce conclusions that clarify the picture of the object being studied. Conclusions based on the results of research analysis using descriptive-comparative research methods with a qualitative approach. It can be concluded that from the 15 articles used to explain that operational costs show a very significant and dominant influence on net profit. This can be identified from the 11 articles that use this component.